Analisis Kinerja Keuangan Unit Simpan Pinjam Koperasi Guru Mangkutala Di Kecamatan Teweh Tengah Kabupaten Barito Utara - Eneng Samsiah; Saladin Ghalib; Rasyidi Rasyidi (Universitas Lambung Mangkurat, 2017)
The purpose of this research is to identify factors which influence financial performance of the Savings and Loans Unit of Guru Mangkutala Cooperative of Kecamatan Teweh Tengah, Kabupaten Barito Utara towards the productive asset quality, management aspect and unoptimal liquidity aspect that may affect the financial performance.The financial performance of the Savings and Loans Unit of Guru Mangkutala Cooperativeis measured with the financial ratio analysis. Good financial performance can be measured from the analysis result to obtain percentages according to the standard established.The guidelines used in evaluating the financial performance of the Savings and Loans Unit of Guru Mangkutala Cooperativearethe standard of the decision of the State Minister of Cooperatives and Small and Middle-Scale Business number 14/Per/M.KUMKM/XII/2009 concerning the guidelines for evaluating the Savings and Loans Unit of Cooperatives. The aspects analysedare capital adequacy, productive asset quality, management, efficiency, liquidity, independence and growth, and cooperative identity. The analysis result shows that productive asset quality, management and liquidity have not been optimal. The result of the research indicates that the main cause of the unoptimal financial performance in productive asset quality aspect is the high percentage of no performance Loans and there is no allocated reservation for risk fund. Inmanagement aspect, there is no long-term planning, no reserved fund policy to abolize Non Performance Loans, no policy to control liquidity and the weakness of human resources. Inliquidity aspect, there is much idle cash. Keywords: financial performance, productive asset quality, management, and liquidity